Teachers Moral Education and Social Competence: Their Influence on Student Character Formation At Madrasah Aliyah Negeri in Padang - Wairisal, Paulus L; Sukarma, I Ketut; Pamungkas, Muhamad Imam; Harefa, Edward; Husnita, Liza; Nazmi, Ranti (Journal of Ecohumanism, 2025)
Quality Human Resources (HR) have behavior that is faithful and devoted to God Almighty. In fostering good HR is the task of education. HR strives to develop aspects of personality both physically and spiritually in students. HR must be formed by teachers to participate in the professional community, devotion, business, or prepare students to become entrepreneurs who are related to the wider community. This study aims to determine whether moral education and social competence have an effect one by one or simultaneously on the formation of student character using quantitative methods using SPSS version 23 with a sample of 127 respondents. The results of this study indicate a significant influence of moral education and social competence of teachers on the formation of students at Madrasah Aliyah Negeri in Padang, both partially and simultaneously. The results of this study have implications for the development of student character by knowing more effective character formation where schools can implement more effective learning strategies to improve character values such as honesty, responsibility, empathy, and cooperation among students. For further research, it is possible to test other variables that can influence the formation of student character, such as parental involvement, social environment, and the use of digital media.